Writing, autography and catastrophe in Mario Bellatin’s work - Castillo Ávila, Antonio (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
This paper proposes a particular reading of the late work by Mario Bellatin, specially his 2013 novel El hombre dinero. It is the goal of this reading to clarify the ways in which this work reaches and questions one of the keys operating modes of the modern literary experience, one which acts as its empty center: the autopoietic impulse of the subject as opus. Beyond any controversy about the generic status of a particular work as autobiographic, Mario Bellatin’s work explores performatively the ways in which literature (as we experience it in creation and reception since its modern institutionalization), has been and continues to be an active excercise within a self-saying, self-representative tension by a subject historically determined by a particular structure: the duality of the merchandise imposed to it by the capitalist society of value.